Compulsory Patent Implementation In Indonesia According to Law No. 6 of 2023 About Job Creation - Nur Aisyah Thalib; Syafrinaldi; Abd Thalib (International Conference On Law And Social Sciences, 2024)
Law Number 6 of 2023 amends the provisions of Article 20 of the Patent Law, (1) Patents must be implemented in Indonesia. (2) Patent implementation as intended in paragraph (1), is as follows: a. implementation of product Patents, which includes making, importing, or licensing products granted a Patent; b. implementation of a process Patent, which includes making, licensing, or importing products resulting from a Patented process; or c. implementation of Patents-methods, systems and uses which includes making, importing or licensing products resulting from methods, systems and uses granted a Patent. The legal research method used is the normative legal research method, which focuses on literature study using various secondary data sources. With the implementation of these changes, we can see that the definition of patent enforcement has become fragmented. The new Article 20 breaks down Patent enforcement into several activities, and uses the word "or" in its formulation, such as "includes making, importing or licensing products granted a Patent". Thus, by only doing one of these things, the obligation to implement a patent in Indonesia can be fulfilled, so that fulfilling the provisions of Article 20 paragraph (1) becomes easier. Patent holders are no longer required to make products in Indonesia, so they do not create factories or offices in Indonesia, which means there is no transfer of technology and knowledge, or employment. In fact, the goals of transferring technology and knowledge, as well as absorbing labor, are the most important goals contained in Article 20 of the Patent Law. With the new formulation of Article 20, this objective seems to be removed from the Patent Law.